SOEWARNI PRINGGODIGDO: PERJUANGAN PEREMPUAN DALAM MAJALAH SEDAR (1930-1932) - Sri Martini; Ratu Husmiati; Fina Lazuardi (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
Abstract. FINA LAZUARDI. SOEWARNI PRINGGODIGDO: WOMEN'S STRUGGLE IN SEDAR MAGAZINE (1930-1932). History Education Study Program, Faculty of Social Sciences, Jakarta State University, January 2023. This study tries to clarify Soewarni's ideas regarding the fight for women's equal rights in the political, sociocultural, and educational spheres as they were presented in Sedar magazine. In this historical study, feminist theory is used as an analytical tool to present Soewarni's ideas in Sedar magazine. The findings are presented in a descriptive-analytic format. The historical research method consists of four stages: heuristics (source collection), verification (source criticism), interpretation and historiography. The results of this study explain the spirit of renewal of the struggle for the women's movement pioneered by Soewarni through Istri Sedar. The Equal rights and obligations between men and women will only be obtained if women cooperate in the struggle for independence. Abstrak. FINA LAZUARDI. SOEWARNI PRINGGODIGDO: PERJUANGAN PEREMPUAN DALAM MAJALAH SEDAR (1930-1932). Program Studi Pendidikan Sejarah, Fakultas Ilmu Sosial, Universitas Negeri Jakarta, Januari 2023. Penelitian ini bertujuan untuk menjelaskan pemikiran Soewarni yang dituangkan dalam majalah Sedar untuk memperjuangkan kesetaraan hak-hak perempuan dalam bidang politik, sosial-budaya, dan pendidikan. Penelitian ini menggunakan metode sejarah dan hasilnya disajikan dalam bentuk deskriptif-analitik yang menggunakan teori feminisme sebagai pisau analisis untuk menampilkan pemikiran Soewarni dalam majalah Sedar. Metode penelitian sejarah terdiri dari empat tahap yaitu: heuristik (pengumpulan sumber), verifikasi (kritik sumber), interpretasi dan historiografi. Hasil penelitian ini menjelaskan mengenai semangat pembaharuan perjuangan pergerakan perempuan yang dipelopori oleh Soewarni melalui Istri Sedar. Kesamaan hak dan kewajiban antara laki-laki dan perempuan hanya akan didapat jika perempuan ikut bekerjasama dalam berjuang meraih kemerdekaan.